Increasing numbers of global change stressors reduce soil carbon worldwide - Sáez Sandino, Tadeo; Maestre, Fernando T.; Berdugo Vega, Miguel; Gallardo, Antonio; Plaza, César; García Palacios, Pablo; Guirado, Emilio; Zhou, Guiyao; Mueller, Carsten W.; Tedersoo, Leho; Crowther, T. W.; Delgado Baquerizo, Manuel (Nature Climate Change, 2024)
F.T.M. was supported by European Research Council grant number 647038 (BIODESERT), Generalitat Valenciana grant number CIDEGENT/2018/041, by the Spanish Ministry of Science and Innovation (grant numbers EUR2022-134048 and PID2020-116578RB-I00) and by the contract between ETH Zurich and University of Alicante “Mapping terrestrial ecosystem structure at the global scale”. E.G. acknowledges funding from Generalitat Valenciana and Europen Social Fund (grant number APOSTD/2021/188). F.T.M. also acknowledges support from the King Abdullah University of Science and Technology (KAUST) and the KAUST Climate and Livability Initiative. T.S.-S., A.G. and M.D.-B. are supported by grant number TED2021-130908B-C41 (URBANCHANGE). M.D.-B. was also supported by the European Research Council (ERC) grant number 647038 (BIODESERT), BES grant agreement number LRB17\1019 (MUSGONET), the innovation programme under Marie Sklodowska-Curie grant agreement number 702057 (CLIMIFUN), Ramón y Cajal grant number RYC2018-025483-I, a project from the Spanish Ministry of Science and Innovation (grant number PID2020-115813RA-I00; SOIL4GROWTH) and project PAIDI 2020 from the Junta de Andalucía (grant number P20_00879). C.W.M. acknowledges funding for the research provided by the NSF Postdoctoral Fellowship in Polar Regions Research (grant number 0852036), the German Science Foundation (DFG) for financial support in the frame of the “Initiation of International Collaboration” (grant number MU 3021/2-1) and funding within the DFG Priority Programme 1158 “Antarctic Research with Comparable Investigations in Arctic Sea Ice Areas” (grant number MU 3021/8-1). M.B. acknowledges funding from Spanish Ministry of Science and Innovation through a Ramón y Cajal Fellowship (# RYC2021-031797-I). Soils support a vast amount of carbon (C) that is vulnerable to climatic and anthropogenic global change stressors (for example, drought and human-induced nitrogen deposition). However, the simultaneous effects of an increasing number of global change stressors on soil ...